Transcriptome innovations in primates revealed by single-molecule long-read sequencing - Ferrández-Peral, Luis; Zhan, Xiaoyu; Alvarez-Estape, Marina; Chiva, Cristina; Esteller-Cucala, Paula; García-Pérez, Raquel; Julià, Eva; Lizano, Esther; Fornas, Òscar; Sabidó, Eduard; Li, Qiye; Marquès-Bonet, Tomàs; et al. (Genome Research, 2022)
Transcriptomic diversity greatly contributes to the fundamentals of disease, lineage-specific biology, and environmental adaptation. However, much of the actual isoform repertoire contributing to shaping primate evolution remains unknown. Here, we combined deep long- and short-read sequencing complemented with mass spectrometry proteomics in a panel of lymphoblastoid cell lines (LCLs) from human, three other great apes, and rhesus macaque, producing the largest full-length isoform catalog in primates to date. Around half of the captured isoforms are not annotated in their reference genomes, significantly expanding the gene models in primates. Furthermore, our comparative analyses unveil hundreds of transcriptomic innovations and isoform usage changes related to immune function and immunological disorders. The confluence of these evolutionary innovations with signals of positive selection and their limited impact in the proteome points to changes in alternative splicing in genes involved in immune response as an important target of recent regulatory divergence in primates.
10.1101/gr.276395.121